Gender differences in ESG investment preferences: A literature review of demographic factors in sustainable investing - Rautakoura, Rosa (My University, 2026)
The purpose of this thesis is to examine how demographic factors, such as gender, education, and age, influence ESG investment preferences across both developed and emerging markets. Understanding what drives individual investors toward ESG investing has become increasingly relevant as sustainable finance continues to grow. Theories such as social role theory, human capital theory, and socioemotional selectivity theory suggest that these demographic factors shape investment values and behaviour, but empirical evidence shows varying results depending on the market context. In developed markets, the existing literature broadly shows that female, more educated, and younger investors tend to prioritize ESG more than their counterparts. The findings in emerging markets are not the same, since the patterns are weaker or sometimes point in the opposite direction, particularly for gender. Women’s reported lower ESG knowledge and financial confidence in these contexts seem to limit their engagement, suggesting that access to financial education plays an important role. The findings show that demographic factors do not work independently and that their effect on ESG preferences is also dependent on the cultural and economic environment in which investors operate.

Tämän tutkielman tarkoituksena on tarkastella, miten demografiset tekijät, kuten sukupuoli, koulutus ja ikä, vaikuttavat ESG-sijoituspreferensseihin sekä kehittyneillä että kehittyvillä markkinoilla. Ymmärrys siitä, mitkä tekijät ohjaavat yksityissijoittajia ESG-sijoittamiseen, on tullut yhä merkityksellisemmäksi kestävän rahoituksen jatkuvan kasvun myötä. Teoriat, kuten sosiaalisten roolien teoria, inhimillisen pääoman teoria ja sosioemotionaalisen valikoivuuden teoria, viittaavat siihen, että nämä demografiset tekijät muokkaavat sijoitusarvoja ja -käyttäytymistä, mutta empiirinen näyttö osoittaa vaihtelevia tuloksia markkinakontekstista riippuen. Kehittyneillä markkinoilla olemassa oleva kirjallisuus osoittaa laajasti, että naissijoittajat, korkeammin koulutetut sijoittajat ja nuoremmat sijoittajat painottavat ESG-tekijöitä enemmän kuin vertailuryhmänsä. Kehittyvillä markkinoilla tulokset eivät ole samanlaisia, sillä havaitut yhteydet ovat heikompia tai joissain tapauksissa jopa päinvastaisia, erityisesti sukupuolen osalta. Tutkimusten viittaama naisten vähäisempi ESG-tietämys ja heikompi taloudellinen itsevarmuus näissä konteksteissa näyttävät rajoittavan heidän osallistumistaan, mikä viittaa siihen, että talouskoulutuksen saatavuudella on tärkeä rooli. Tulokset osoittavat, että demografiset tekijät eivät vaikuta toisistaan riippumatta ja että niiden vaikutus ESG-preferensseihin riippuu myös siitä kulttuurisesta ja taloudellisesta ympäristöstä, jossa sijoittajat toimivat.
Keywords: responsible investing; investments; investment activities; societal responsibility; gender; corporate responsibility; investors; gender differences; sustainable development; investments (economics); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|